GENOTYPIC CHARACTERIZATION OF PSEUDOMONAS AERUGINOSA FROM POINT-OF-SALES DEVICES IN LOKOJA, NIGERIA - Jibola-Shittu, Motunrayo Yemisi; Odewale, Gbolabo; Luka, Mela Ilu; Odoh, Joshua Atabo; Bala, Hannatu Eleojo Mary; Kehinde, Aminat Bukola (FUDMA Journal of Sciences, 2025)
The presence of Pseudomonas aeruginosa on shared frequently used surfaces, such as Point-of-Sales (POS) devices present serious public health problem. This study assessed P. aeruginosa on POS devices frequently used within Lokoja metropolis, with the aim of determining the presence of antibiotic resistance and virulence genes in the P. aeruginosa. Following standard procedures, Seventy-two POS devices were randomly sampled using sterile swabs soaked in peptone water and cultured on sterile agar plates. Biochemical characterization of isolates was carried out while antibiotics susceptibility testing was carried out using the Kirby-Bauer disc diffusion method. Some resistance and virulence genes of P. aeruginosa were detected using polymerase chain reaction (PCR) assay. Bacterial isolates were characterized as Staphylococcus aureus (32.4%), Klebsiella pneumoniae (21.9%), Pseudomonas aeruginosa (17.2%), Escherichia coli (14.2%), Bacillus subtilis (10.1%), Enterobacter spp. (2.4 %) and Enterococcus sp. (1.8%). Pseudomonas aeruginosa isolates displayed antibiotic resistance against tetracyclines (58.6%), followed by ceftazidime (51.7%), gentamicin (48.3%), cefepime (48.3%), ceftriaxone (48.3%), cefoxitin (44.8%), levofloxacin (41.2%), ciprofloxacin (37.9%), amoxicillin-clavulanic acid (37.9%) and imipenem (24.1%). For the virulence genes, 72.4%, 38%, 28% of the Pseudomonas aeruginosa strains were positive for OprL, toxA and lasB, respectively while for the antibiotic resistance genes, 14% were positive for blaVIM and 10.3% for blaIMP. This study reveals the presence of pathogenic P. aeruginosa on POS devices with their virulence genes and antibiotics resistance genes. This emphasizes the health threat associated with shared surfaces such as the POS devices. Thus, users must maintain sanitary and hygienic practices while using these devices.
Keywords: Radiation; Radio-frequency; Smartphones; Spectrum Analyzer; Human health